Pola Pembinaan Rohani Berdasarkan Efesus 6:4 Dan Korelasinya Dalam Mendidik Perilaku Anak Di Panti Asuhan Claresta Medan - Tiur Imeldawati; Elisabet Savitri Lukita Dewi; Agripa Sitepu (Jurnal Christian Humaniora, 2021)
Abstract:Spiritual development of children is a very important thing. Even from an early age, parents are expected to have nurtured their children so that in the future they can have good and commendable behavior. The author highlights this from the passage of Ephesians 6:4 because this verse clearly describes the relationship between parents and children. And related to orphanage children who do have differences with children in general who are raised and educated by their biological parents, children in orphanages have their own problems so that they are not raised in their family and are not cared for by their biological parents. them but by the caretaker of the orphanage who is also their spiritual parent. Through the pattern of spiritual development carried out in this orphanage, it is hoped that it will produce a quality generation, even though they have poor backgrounds. The excavation of Ephesians 6:4 becomes the biblical basis and this research is carried out at the same time to see the implementation of the pattern of spiritual formation that has been carried out so far, and the expected results. In which case are the shortcomings or weaknesses in implementing the pattern that has been discussed so far.Keywords: Pattern, Spiritual Development, Behavior, Claresta  Abstrak:Pembinaan rohani anak merupakan suatu hal yang sangat penting. Bahkan sejak dini para orangtua diharapkan telah membina anak-anak mereka untuk kelak bisa memiliki perilaku yang baik dan terpuji. Penulis menyoroti hal ini dari nas Efesus 6:4 dikarenakan ayat ini memuat tentang hubungan orangtua dan anak secara jelas. Dan terkait dengan anak-anak panti asuhan yang memang memiliki perbedaan dengan anak-anak pada umumnya yang dibesarkan dan dididik oleh orangtua kandung mereka, anak-anak di panti asuhan memiliki masalah tersendiri sehingga mereka tidak dibesarkan di dalam keluarga mereka dan tidak diasuh oleh orangtua kandung mereka melainkan oleh pengurus panti asuhan yang sekaligus menjadi orangtua rohani mereka. Melaluo pola pembinaan rohani yang dilakukan di pantu asuhan ni diharapkan dapat menghasilkan generasi yang berkualitas, meskipun mereka memiliki latar belakang yang kurang baik. Penggalian Efesus 6:4 menjadi dasar alkitabiahnya dan riset ini dilakukan sekaligus untuk melihat pengimplementasian pola pembinaan rohani yang telah dilakukan selama ini, dan hasil yang diharapkan. Dalam hal manakah yang menjadi kekuarangan atau kelemahan dalam pengimplementasian pola yang selama ini sudah diterapkan. Kata Kunci: Pola, Pembinaan Rohani, Perilaku, Claresta